Negative electrode active material and preparation method thereof, secondary battery and electric device
By using nano-sized negative electrode active materials and using the combined structure of the core, intermediate layer and carbon layer, the problems of volume expansion and poor conductivity of the negative electrode materials of lithium-ion batteries during the cycle are solved, and the effects of high capacity, good rate performance and long cycle life are achieved.
Patent Information
- Application Number
- CN202411297332.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2025-04-18
AI Technical Summary
The negative electrode material of the existing lithium-ion battery has a high volume expansion during the cycle, making it difficult to form a stable SEI film, and the electron conductivity is poor, which limits the development of high-energy density lithium-ion batteries.
A negative electrode active material with a nano-sized particle size includes a core, an intermediate layer coated on the surface of the core, and a carbon layer coated on the surface of the intermediate layer. The material of the core may be silicon, silicon dioxide or a first metal that can be embedded with deliferated lithium, and the material of the intermediate layer is a second metal that can be embedded with deliferated lithium, and the second metal is different from the first metal. The material was prepared by the DC arc discharge plasma method.
The capacity, rate performance and cycle life of the negative electrode active material are improved, and the volume expansion of the core when it is embedded with Li+ is suppressed or buffered by the combination of the intermediate layer and the carbon layer, and the electronic conductivity is enhanced.
Smart Images

Figure CN119852347A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium batteries, and in particular to a negative electrode active material and a preparation method thereof, a secondary battery and an electrical device. Background Art
[0002] In recent years, lithium-ion batteries have been widely used in electronic products, electric vehicles and power grid storage systems as a green energy storage device due to their advantages such as high operating voltage, long cycle life, low self-discharge rate and no memory effect.
[0003] As a traditional negative electrode material for lithium-ion batteries, graphite has a low theoretical specific capacity and is difficult to meet market demand, which seriously limits the development of high-energy-density lithium-ion batteries. Silicon stands out among the candidates for new negative electrode materials because of its moderate lithium insertion potential and high theoretical specific capacity. However, during the cycle, the volume expansion of silicon negative electrode is high, which makes it difficult to form a stable SEI film on the surface of the active material. In addition, silicon has poor electronic conductivity, which hinders the industrialization of silicon negative electrode. Metal or alloy negative electrode materials have a theoretical specific capacity far exceeding that of graphite negative electrode, but when the lithium deposition capacity is high, there are problems such as dendrite growth and volume expansion.
[0004] Therefore, how to obtain a high-capacity negative electrode active material, and how to make a lithium-ion battery prepared from the negative electrode active material have better rate performance and cycle life is an urgent problem to be solved in the art. Summary of the invention
[0005] The present application is made in view of the above-mentioned problems, and its purpose is to provide a high-capacity negative electrode active material, and the lithium-ion battery prepared from the negative electrode active material has better rate performance and cycle life.
[0006] In order to achieve the above-mentioned objectives, the present application provides a negative electrode active material and a preparation method thereof, a secondary battery and an electrical device.
[0007] The first aspect of the present application provides a negative electrode active material, wherein the particle size of the negative electrode active material is less than or equal to 200 nm, and the negative electrode active material comprises: a core, an intermediate layer coated on the surface of the core, and a carbon layer coated on the surface of the intermediate layer;
[0008] The material of the core includes silicon, silicon dioxide or a first metal capable of inserting and extracting lithium, and the material of the intermediate layer includes a second metal capable of inserting and extracting lithium, and the second metal is different from the first metal.
[0009] Therefore, the negative electrode active material provided in the present application not only has a high capacity based on its nanoscale particle size and the coordination of each layer in the core-shell structure, but also the lithium ion battery prepared from the negative electrode active material has better rate performance and cycle life.
[0010] In any embodiment, the negative electrode active material has a spherical morphology. The spherical morphology is conducive to uniform expansion of the negative electrode active material during expansion, thereby improving the cycle performance.
[0011] In any embodiment, the melting point of the inner core is greater than the melting point of the middle layer. Under this condition, the negative electrode active material can be prepared by a direct current arc discharge plasma method.
[0012] In any embodiment, the core is intercalated and deintercalated with Li + The volume expansion rate of the intermediate layer is greater than that of the intercalation and deintercalation of Li + The volume expansion rate of the middle layer is + The volume expansion rate of the carbon layer is greater than that of the carbon layer during the insertion and extraction of Li + The volume expansion rate of the core can be suppressed or buffered by the intermediate layer during the insertion and extraction of Li + The volume expansion is beneficial to improving the stability of the negative electrode active material and increasing the cycle life of the lithium ion battery prepared from the negative electrode active material.
[0013] In any embodiment, the interlayer electronic conductivity is 10 7 S / m-10 22 Since silicon has poor electronic conductivity, controlling the electronic conductivity of the middle layer within the above range and providing the outermost layer as a carbon layer is beneficial to improving the electronic conductivity of silicon, thereby improving the rate performance of a lithium-ion battery prepared from the negative electrode active material.
[0014] In any embodiment, the discharge specific capacity of the core and the middle layer is greater than 900 mAh / g respectively. Controlling the discharge specific capacity of the core and the middle layer within the above range is conducive to controlling the final negative electrode active material to have a high specific capacity.
[0015] In any embodiment, the core is silicon and the middle layer is tin. When tin is used as the middle layer to coat the surface of the silicon core, it can not only effectively improve the electronic conductivity of silicon, but also help to inhibit or buffer the volume expansion of the silicon core during the process of lithium insertion and extraction, which is beneficial to improve the stability of the negative electrode active material and enhance the electrochemical performance of the lithium ion battery prepared by the negative electrode active material.
[0016] In any embodiment, the core is aluminum and the middle layer is tin. The negative electrode active material of aluminum core-tin middle layer-carbon layer has a higher capacity, and the lithium ion battery prepared from the negative electrode active material has better rate performance and cycle life.
[0017] In any embodiment, the mass percentage of the core in the negative electrode active material is 70%-80%, the mass percentage of the middle layer in the negative electrode active material is 15%-20%, and the mass percentage of the carbon layer in the negative electrode active material is 5%-10%. Controlling the mass percentages of the core, the middle layer, and the carbon layer in the negative electrode active material within the above range can achieve a better synergistic effect of the core, the middle layer, and the carbon layer, so that the performance such as capacity and cycle life can be effectively improved.
[0018] In any embodiment, the thickness of the intermediate layer is 5 nm to 8 nm; and / or,
[0019] The thickness of the carbon layer is 3-5 nm. Controlling the thickness of the intermediate layer and the carbon layer within the above range is conducive to taking into account both better capacity and cycle performance.
[0020] In any embodiment, the Dv50 of the negative electrode active material is 50nm-100nm, and the Dv90 is 120nm-150nm, which is conducive to the rapid diffusion of lithium ions inside the powder during charging and discharging and basically does not cause powder agglomeration.
[0021] In any embodiment, the powder compaction density of the negative electrode active material at 3T is 1.3 g / cm 3 -1.7g / cm 3 .
[0022] The second aspect of the present application also provides a method for preparing a negative electrode active material, which comprises:
[0023] Mixing components for forming a core and an intermediate layer and pressing them into a block, wherein the component for forming the core includes silicon, silicon dioxide or a first metal capable of inserting and extracting lithium, and the component for forming the intermediate layer includes a second metal capable of inserting and extracting lithium, and the melting point of the core is greater than the melting point of the intermediate layer;
[0024] The block is placed as an anode target at the anode, a tungsten rod or a carbon rod is used as a cathode, and a negative electrode active material is obtained by direct current arc discharge plasma treatment in an atmosphere of hydrogen, an inert gas and a gaseous carbon source;
[0025] The gaseous carbon source includes at least one of alkanes, alkenes and alkynes.
[0026] Therefore, the preparation method provided in the present application can use the direct current arc method to obtain a negative electrode active material with a spherical morphology with controllable product morphology, uniform particle size, high capacity, good cycle stability, excellent rate performance and a particle size of 200nm or less in one step. The preparation steps are simple and the preparation process is safe and stable. In addition, the above method can form a uniform and complete intermediate layer in situ on the surface of the inner core, and a uniform and complete carbon layer in situ on the surface of the intermediate layer, which is beneficial to further improve the product structural stability and enhance the electrochemical performance of lithium-ion batteries prepared with the negative electrode active material.
[0027] In any embodiment, the gaseous carbon source is calculated as methane, and the volume ratio of the inert gas, hydrogen and gaseous carbon source is 1.5-2.5:1:0.4-0.6. Controlling the volume ratio of the inert gas, hydrogen and gaseous carbon source within the above range can not only promote the evaporation of the target material and form particles with a suitable particle size, but also facilitate the formation of a carbon layer of suitable thickness.
[0028] The third aspect of the present application provides a secondary battery, comprising the negative electrode active material of the first aspect of the present application or the negative electrode active material prepared by the preparation method provided by the third aspect of the present application.
[0029] A fourth aspect of the present application provides an electrical device, comprising the secondary battery of the third aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a SEM image of the negative electrode active material provided in Example 1;
[0031] Figure 2 TEM image of the negative electrode active material provided in Example 1;
[0032] Figure 3 A cycle performance diagram of a negative electrode sheet containing the negative electrode active material provided in Example 1;
[0033] Figure 4 A coulombic efficiency diagram of a negative electrode sheet containing the negative electrode active material provided in Example 1;
[0034] Figure 5 A rate performance diagram of a negative electrode sheet containing the negative electrode active material provided in Example 1;
[0035] Figure 6 is a schematic diagram of a secondary battery according to an embodiment of the present application;
[0036] Figure 7 yes Figure 6 An exploded view of a secondary battery according to an embodiment of the present application is shown;
[0037] Figure 8 is a schematic diagram of a battery module according to an embodiment of the present application;
[0038] Fig. 9 is a schematic diagram of a battery pack according to an embodiment of the present application;
[0039] Fig.10 yes Fig. 9 An exploded view of a battery pack according to an embodiment of the present application is shown;
[0040] Fig.11 FIG. 1 is a schematic diagram of an electric device using a secondary battery according to an embodiment of the present application as a power source.
[0041] Description of reference numerals:
[0042] 1-battery pack; 2-upper box; 3-lower box; 4-battery module; 5-secondary battery; 51-housing; 52-electrode assembly; 53-cover plate. DETAILED DESCRIPTION
[0043] Below, the embodiments of the positive electrode active material and its manufacturing method, positive electrode sheet, secondary battery, battery module, battery pack and electrical device of the present application are specifically disclosed with appropriate reference to the drawings. However, there are cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0044] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0045] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0046] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0047] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, a method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, a method may also include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0048] If there is no special explanation, the "include" and "comprising" mentioned in this application represent open-ended or closed-ended expressions. For example, "include" and "comprising" may represent that other components not listed may also be included or only listed components may be included or only listed components may be included.
[0049] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0050] In order to improve the quality of a high-capacity negative electrode active material and to obtain a lithium-ion battery prepared from the negative electrode active material with better rate performance and cycle life, silicon and a metal capable of inserting and removing lithium are usually first formed into a composite and then carbon-coated on the surface. The particle size of the resulting negative electrode active material is micron-level and the performance improvement is limited.
[0051] Based on this, the first aspect of the embodiment of the present application provides a negative electrode active material, the particle size of the negative electrode active material is less than or equal to 200nm, the negative electrode active material includes a core, an intermediate layer coated on the surface of the core, and a carbon layer coated on the surface of the intermediate layer;
[0052] The melting point of the core is greater than that of the middle layer, the core is made of silicon, silicon dioxide or a first metal capable of inserting and removing lithium, the middle layer is made of a second metal capable of inserting and removing lithium, and the second metal is different from the first metal.
[0053] The particle size of the negative electrode active material in the present application is less than or equal to 200nm. That is, the particle size of the largest particle in the negative electrode active material in the present application is less than or equal to 200nm. Controlling the maximum particle size of the negative electrode active material within 200nm can produce nano effects such as surface effect, small size effect and macro quantum tunneling effect, which is beneficial to improving the capacity, rate performance and cycle performance of the lithium ion battery prepared from the negative electrode active material.
[0054] The first metal and the second metal that can embed and extract lithium include but are not limited to metal elements such as tin, antimony, aluminum, magnesium, zinc, etc., or alloys of at least two of them. Those skilled in the art can choose according to actual needs.
[0055] In summary, the negative electrode active material of the present application not only has a high capacity based on its nanoscale particle size and the coordination of each layer in the core-shell structure, but also the lithium ion battery prepared from the negative electrode active material has better rate performance and cycle life.
[0056] In some embodiments, the negative electrode active material has a spherical morphology.
[0057] It is understandable that a certain amount of expansion is allowed during the use of the negative electrode active material, and the spherical morphology is conducive to uniform expansion of the negative electrode active material during expansion, thereby improving the cycle performance. The spherical morphology can be obtained through SEM images.
[0058] In some embodiments, the melting point of the inner core is greater than the melting point of the middle layer.
[0059] Under this condition, the negative electrode active material can be prepared by a DC arc discharge plasma method.
[0060] In some embodiments, the inner core is exposed to Li + The volume expansion rate of the intermediate layer is greater than that of the intercalation and deintercalation of Li + The volume expansion rate of the middle layer is + The volume expansion rate of the carbon layer is greater than that of the carbon layer during the insertion and extraction of Li + volume expansion rate.
[0061] Using the intermediate layer to insert and remove Li + The volume expansion rate of the core is smaller than that of the core during the insertion and extraction of Li + The volume expansion rate can be suppressed or buffered by the intermediate layer during the insertion and extraction of Li + The volume expansion occurring during the process is beneficial to improving the stability of the negative electrode active material and increasing the cycle life of the lithium-ion battery prepared from the negative electrode active material.
[0062] It is understandable that the discharge specific capacity of the core and the intermediate layer, as well as the Li +The volume expansion rate is related to the composition of the core and the middle layer. The discharge capacity and Li insertion and extraction can be confirmed based on the composition and related technologies. + volume expansion rate.
[0063] In some embodiments, the inner core is silicon or silicon dioxide.
[0064] That is, at this time, the negative electrode active material is, from the inside to the outside, a silicon / silicon dioxide core-an intermediate layer formed by a second metal capable of inserting and removing lithium-a carbon layer.
[0065] On the one hand, the second metal has better electronic conductivity, which can increase the conductivity of the negative electrode active material, which is beneficial to accelerate the ion-electron transfer kinetics, thereby improving the rate performance of the lithium-ion battery prepared by the negative electrode active material. On the other hand, silicon is usually + The volume expansion rate during the insertion and extraction reaction of the negative electrode active material is greater than that of the metal. Therefore, with silicon as the core, the intermediate layer formed by the second metal and the carbon layer can be used for double buffering and protection, which is beneficial to improving the lithium-ion battery prepared by the negative electrode active material to have better rate performance and cycle life.
[0066] In some embodiments, the interlayer electronic conductivity is 10 7 S / m-10 22 S / m.
[0067] Since silicon has poor electronic conductivity, controlling the electronic conductivity of the middle layer within the above range and providing the outermost layer as a carbon layer is beneficial to improving the electronic conductivity of silicon, thereby improving the rate performance of the lithium-ion battery prepared from the negative electrode active material.
[0068] For example, the interlayer electronic conductivity is 10 7 S / m, 10 8 S / m, 10 9 S / m, 10 10 S / m, 10 11 S / m, 10 12 S / m, 10 13 S / m, 10 14 S / m, 10 15 S / m, 10 16 S / m, 10 17 S / m, 10 18 S / m, 10 19 S / m, 10 20 S / m, 10 21 S / m, 10 22 Any value of S / m or between any two values.
[0069] In some embodiments, the discharge specific capacity of the inner core and the intermediate layer are each greater than 900 mAh / g.
[0070] By controlling the discharge specific capacity of the core and the intermediate layer within the above range, it is beneficial to control the final negative electrode active material to have a high specific capacity.
[0071] It should be noted that the discharge specific capacity of the core may be greater than the discharge specific capacity of the middle layer, or may be less than or equal to the discharge specific capacity of the middle layer, which is not limited here.
[0072] In some embodiments, the core is silicon and the middle layer is tin.
[0073] Metallic tin can not only contribute to the capacity of lithium ion insertion and extraction, thereby increasing the capacity of the negative electrode active material, but metallic tin is also a good conductive material, and its expansion rate is smaller than that of the silicon core. Therefore, after using tin as an intermediate layer to coat the surface of the silicon core, it can not only effectively improve the electronic conductivity of silicon, but also help to inhibit or buffer the volume expansion of the silicon core during the process of lithium insertion and extraction, which is beneficial to improve the stability of the negative electrode active material and enhance the electrochemical performance of the lithium-ion battery prepared from the negative electrode active material.
[0074] In some embodiments, the inner core is aluminum and the middle layer is tin.
[0075] That is, at this time, the negative electrode active material is aluminum core-tin middle layer-carbon layer from the inside to the outside. The negative electrode active material has a higher capacity, and the lithium ion battery prepared from the negative electrode active material has better rate performance and cycle life.
[0076] In some embodiments, the mass percentage of the core in the negative electrode active material is 70%-80%, the mass percentage of the intermediate layer in the negative electrode active material is 15%-20%, and the mass percentage of the carbon layer in the negative electrode active material is 5%-10%.
[0077] It can be understood that the sum of the mass percentages of the inner core, the middle layer and the carbon layer in the negative electrode active material is 100%.
[0078] Since both the inner core and the middle layer can insert and extract lithium to provide capacity, the higher the mass percentage of the middle layer and the inner core, the higher the capacity. Especially when the inner core is silicon, its mass percentage will obviously affect the capacity of the negative electrode active material. However, excessive mass percentage will lead to volume expansion that cannot be effectively alleviated. Therefore, controlling the mass percentage of the inner core, the middle layer, and the carbon layer in the negative electrode active material within the above range can make the inner core, the middle layer, and the carbon layer achieve better synergistic effects, so that the capacity, cycle life and other performance can be effectively improved.
[0079] Exemplarily, the mass percentage of the core in the negative electrode active material is any one of 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80% or between any two values.
[0080] Exemplarily, the mass percentage of the intermediate layer in the negative electrode active material is any value of 15%, 1617%, 18%, 19%, 20%, or between any two values.
[0081] Exemplarily, the mass percentage of the carbon layer in the negative electrode active material is any one of 5%, 6%, 7%, 8%, 9%, 10%, or between any two values.
[0082] In some embodiments, the thickness of the intermediate layer is 5 nm to 8 nm; and / or,
[0083] The thickness of the carbon layer is 3-5 nm.
[0084] It can be understood that the thickness here refers to the average thickness. The TEM image of the negative electrode active material can be obtained. A total of 20 points are selected from different parts of the layer to be tested (intermediate layer or carbon layer). After obtaining the thickness of the 20 points, the average thickness is calculated as the thickness of the layer to be tested.
[0085] If the thickness of the intermediate layer is too thick, it is easy to limit the transmission of lithium ions into the material, resulting in a low capacity of the material. If the thickness is too thin, it cannot effectively improve the electronic conductivity. Therefore, controlling the thickness of the intermediate layer within the above range is conducive to taking into account both better capacity and cycle performance. Exemplarily, the thickness of the intermediate layer is any value among 5nm, 6nm, 7nm, 8nm or between any two values.
[0086] Since metals, silicon dioxide and silicon that can insert and remove lithium all have volume expansion problems, a carbon layer is introduced as a buffer matrix in the outermost layer to buffer the volume changes of the inner core and the middle layer as the active unit. This is not only conducive to forming a stable SEI film and reducing the thickness of the SEI film, but also can reduce interfacial side reactions. However, if the thickness of the carbon layer is too thin, it cannot effectively buffer and inhibit the deformation of the internal active material. If it is too thick, the carbon content will be too high. Since the lithium insertion capacity of carbon is lower than that of silicon and metals that can insert and remove lithium, the capacity of the negative electrode active material is reduced. Therefore, controlling the thickness of the carbon layer within the above range is beneficial to the negative electrode active material having better electrochemical properties.
[0087] Exemplarily, the thickness of the carbon layer is any value of 3.0 nm, 3.5 nm, 4.0 nm, 4.5 nm, 5.0 nm, or between any two values.
[0088] In some embodiments, the negative electrode active material has a Dv50 of 50 nm to 100 nm, and a Dv90 of 120 nm to 150 nm.
[0089] Dv50 and Dv90 both have meanings known in the art and can be tested using methods known in the art. For example, a laser diffraction particle size distribution measuring instrument is used according to the particle size distribution laser diffraction method (specifically, refer to GB / T19077-2016) to measure. Wherein Dv50 refers to the particle size when the cumulative volume in the particle size distribution measurement by laser scattering method starts from the small diameter at 50%, and Dv90 refers to the particle size when the cumulative volume in the particle size distribution measurement by laser scattering method starts from the small diameter at 90%.
[0090] Generally, the smaller the particle size, the faster the lithium ions diffuse inside the powder during charge and discharge, and the better the battery performance. However, considering that the smaller the particle size, the higher the surface energy of the nanoparticles, which will cause powder agglomeration, the range defined above is preferred.
[0091] Illustratively, the Dv50 of the negative electrode active material is any one of 50 nm, 55 nm, 60 nm, 65 nm, 70 nm, 75 nm, 80 nm, 85 nm, 90 nm, 95 nm, and 100 nm, or between any two values.
[0092] Exemplarily, the Dv90 of the negative electrode active material is any one of 120 nm, 125 nm, 130 nm, 135 nm, 140 nm, 145 nm, 150 nm or between any two values. In some embodiments, the powder compaction density of the negative electrode active material at 3 T is 1.3 g / cm 3 -1.7g / cm 3 .
[0093] For example, the powder compaction density of the negative electrode active material at 3T is 1.3 g / cm 3 , 1.4g / cm 3 , 1.5g / cm 3 , 1.6g / cm 3 , 1.7g / cm 3 Any value in or between any two values.
[0094] The present application also provides a method for preparing the above-mentioned negative electrode active material, which comprises:
[0095] Mixing components for forming a core and an intermediate layer and pressing them into a block, wherein the component for forming the core includes silicon, silicon dioxide or a first metal capable of inserting and extracting lithium, and the component for forming the intermediate layer includes a second metal capable of inserting and extracting lithium, and the melting point of the core is greater than the melting point of the intermediate layer;
[0096] The block is placed as an anode target at the anode, a tungsten rod or a carbon rod is used as a cathode, and a negative electrode active material is obtained by direct current arc discharge plasma treatment in an atmosphere of hydrogen, an inert gas and a gaseous carbon source;
[0097] The gaseous carbon source includes at least one of alkanes, alkenes and alkynes.
[0098] It can be understood that placing the block as the anode target on the anode means that during actual use, the block is placed on a conductive metal seat (such as a copper seat) that serves as an anode and is energized in a DC arc reaction chamber. A circuit can be formed between the conductive metal seat and the cathode through the electric arc, thereby realizing the use of the block as the anode target.
[0099] Using a tungsten rod or a carbon rod as the cathode can avoid melting or evaporation of the tungsten rod or the carbon rod during the DC arc discharge plasma treatment process due to their high melting points.
[0100] It can be understood that since the melting point of the inner core is greater than the melting point of the middle layer, the first metal is different from the second metal, wherein the first metal and the second metal that can embed and extract lithium include but are not limited to metal elements such as tin, antimony, aluminum, magnesium, zinc, or alloys of at least two of them, and technicians in this field can make a choice according to actual needs.
[0101] Inert gases include nitrogen and / or argon.
[0102] The DC arc discharge reaction refers to the DC arc generated between the cathode and the anode. The arc flame of the DC arc can reach a high temperature of thousands of degrees Celsius. The arc flame of the DC arc serves as a heat source for the high-energy growth material. With the arc flame as the center of the heat source, there is a certain temperature gradient from the inside to the outside of the heat source, and it gradually decreases. The growth process of the negative electrode active material is completed in this heat source area. First, hydrogen is ionized into hydrogen plasma, in which hydrogen atoms or hydrogen ions easily enter the molten target material, promoting the evaporation of the target material. The plasma formed after the inert gas is ionized has high conductivity. It collides with the material during the nucleation and growth of the material, reduces the surface energy, and promotes nucleation. The components in the target material used to form the core and the middle layer evaporate into gaseous atoms inside the arc flame, and the gaseous carbon source is decomposed into carbon atoms and hydrogen atoms. The melting point of the core is greater than the melting point of the middle layer. Therefore, when the temperature of the heat source first drops to the melting point of the corresponding component of the core, the nanoparticles of the corresponding component of the core begin to spontaneously nucleate and grow. The temperature continues to drop to the melting point of the corresponding components of the middle layer. The corresponding components of the middle layer begin to heterogeneously nucleate on the surface of the nanoparticles serving as the inner core and grow into a coating layer as the middle layer. The carbon atoms decomposed from the gaseous carbon source will further coat the surface of the middle layer to spontaneously form a carbon layer. The powder of the negative electrode active material is finally deposited on the wall of the reaction chamber.
[0103] In summary, the preparation method provided in the present application can use the DC arc method to obtain a negative electrode active material with a spherical morphology with a controllable product morphology, uniform particle size, high capacity, good cycle stability, excellent rate performance and a particle size of 200 nm or less in one step. The preparation steps are simple and the preparation process is safe and stable. In addition, the above method can form a uniform and complete intermediate layer in situ on the surface of the inner core, and a uniform and complete carbon layer in situ on the surface of the intermediate layer, which is beneficial to further improve the product structural stability and enhance the electrochemical performance of lithium-ion batteries prepared with the negative electrode active material.
[0104] For cost considerations and ease of ionization, the gaseous carbon source is at least one of C1-4 alkanes, C1-4 alkynes and C1-4 alkenes, and optionally, the gaseous carbon source is at least one of C1-4 alkanes and C1-2 alkynes. Further optionally, the gaseous carbon source is methane or ethane.
[0105] In some embodiments, the gaseous carbon source is calculated as methane, and the volume ratio of the inert gas, hydrogen and the gaseous carbon source is 1.5-2.5:1:0.4-0.6.
[0106] It is understandable that, since different gaseous carbon sources contain different numbers of C atoms and H atoms, different types of gaseous carbon sources in the present application are all converted to methane.
[0107] Controlling the volume ratio of the inert gas, hydrogen and gaseous carbon source within the above range can not only promote the evaporation of the target material and form particles with a suitable particle size, but also facilitate the formation of a carbon layer with a suitable thickness.
[0108] Exemplarily, the volume ratio of the inert gas to hydrogen is any one of 1.5:1, 1.8:1, 2.0:1, 2.2:1, 2.5:1 or between any two values, the gaseous carbon source is calculated as methane, and the volume ratio of hydrogen to the gaseous carbon source is any one of 1:0.40, 1:0.45, 1:0.50, 1:0.55, 1:0.60 or between any two values.
[0109] In the DC arc discharge plasma treatment, the distance between the anode and the cathode is 10-25 mm, the current is 10-200 A, and the voltage is 5-30 V.
[0110] By controlling the distance between the anode and the cathode within the above range, a stable DC arc can be generated. At the same time, by reasonably selecting the discharge current and voltage, a stable DC arc can be generated, thereby improving the yield while ensuring the safety of preparing the negative electrode active material.
[0111] Exemplarily, the distance between the anode and the cathode is any one of 10 mm, 12 mm, 15 mm, 18 mm, 20 mm, 23 mm and 25 mm, or a range between any two values.
[0112] Exemplarily, the current in the DC arc discharge plasma treatment is any one of 10A, 30A, 50A, 75A, 100A, 125A, 150A, 175A and 200A, etc., or a range between any two values.
[0113] Exemplarily, the voltage in the DC arc discharge plasma treatment is any one value of 5V, 7V, 10V, 15V, 20V, 25V and 30V, etc., or a range between any two values.
[0114] In addition, the secondary battery, battery module, battery pack, and electric device of the present application will be described below with reference to the drawings as appropriate.
[0115] [Secondary battery]
[0116] A second aspect of the embodiments of the present application provides a secondary battery. The present application has no particular limitation on the type of the secondary battery, for example, the secondary battery may be a lithium-ion battery.
[0117] Generally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0118] The present application has no particular restrictions on the type of electrolyte, which can be selected according to actual needs. For example, the electrolyte can be selected from at least one of a solid electrolyte and a liquid electrolyte (i.e., an electrolyte). A secondary battery using an electrolyte, and some secondary batteries using a solid electrolyte.
[0119] [Negative electrode]
[0120] In some embodiments, the negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector. The negative electrode film layer includes the negative electrode active material of the first aspect of the present application.
[0121] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0122] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0123] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0124] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0125] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0126] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0127] In other embodiments, the current collector of the negative electrode plate may generally include a current collector body and an undercoat layer, the undercoat layer may be disposed on at least one side of the current collector body, the undercoat layer substantially does not contain negative electrode active materials, and may include a small amount of carbon material, but the thickness of the coating formed by the carbon material is thin and cannot play the role of negative electrode active materials. In this embodiment, the negative electrode plate may be a plate without a negative electrode active material layer. For a negative electrode plate without a negative electrode active material layer, when the current collector of the negative electrode plate does not contain an undercoat layer, the film layer may be disposed on the surface of at least one side of the current collector; when the current collector of the negative electrode plate includes an undercoat layer, the film layer may be disposed on the surface of the undercoat layer on the side away from the current collector.
[0128] In some embodiments, the film layer may further include a binder, which is used to fix the additive on the negative electrode plate. The type of the binder is not particularly limited, and those skilled in the art may flexibly select the binder according to actual needs.
[0129] [Positive electrode]
[0130] The positive electrode plate includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector.
[0131] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0132] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0133] In some embodiments, when the secondary battery is a lithium-ion battery, the positive electrode active material may adopt a positive electrode active material for lithium-ion batteries that is well known in the art. As an example, the positive electrode active material may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (which can also be abbreviated as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (which can also be abbreviated as NCM 811 )、lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O2) and at least one of its modified compounds, etc. Examples of olivine-structured lithium-containing phosphates may include, but are not limited to, lithium iron phosphate (such as LiFePO4 (which can also be abbreviated as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium manganese iron phosphate, and at least one of a composite material of lithium manganese iron phosphate and carbon.
[0134] In some embodiments, in order to further improve the energy density of the secondary battery, the positive electrode active material for a lithium-ion battery may include a lithium transition metal oxide having the general formula Li a Ni b Co c M d O e A f and one or more of its modified compounds. 0.8 ≤ a ≤ 1.2, 0.5 ≤ b < 1, 0 < c < 1, 0 < d < 1, 1 ≤ e ≤ 2, 0 ≤ f ≤ 1, M is selected from one or more of Mn, Al, Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, and B, and A is selected from one or more of N, F, S, and Cl.
[0135] In some embodiments, by way of example, the positive electrode active material for a lithium-ion battery may include LiCoO2, LiNiO2, LiMnO2, LiMn2O4, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2 (NCM523), LiNi 0.6 Co 0.2 Mn 0.2 O2 (NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811), LiNi 0.85 Co 0.15 Al 0.05One or more of O2, LiFePO4 and LiMnPO4.
[0136] In the present application, the modified compounds of the above-mentioned positive electrode active materials may be the ones subjected to doping modification and / or surface coating modification of the positive electrode active materials.
[0137] As an optional technical method of the present application, the polyanionic compound can be Li 1+x Mn 1-y A y P 1-z R z O4; wherein x is any value in the range of -0.100 to 0.100, y is any value in the range of 0.001 to 0.500, z is any value in the range of 0.001 to 0.100, A includes one or more elements selected from Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb and Ge, and R includes one or more elements selected from B, S, Si and N;
[0138] As an optional technical method of the present application, the polyanionic compound can be Li a A e Mn 1-f B f P 1-g C g O 4-n D n , wherein A includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Nb, Mo, and W; B includes one or more elements selected from the group consisting of Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb, and Ge; C includes one or more elements selected from the group consisting of B, S, Si, and N; D includes one or more elements selected from the group consisting of S, F, Cl, and Br; a is selected from the range of 0.9 to 1.1, e is selected from the range of 0.001 to 0.1, f is selected from the range of 0.001 to 0.5, g is selected from the range of 0.001 to 0.1, n is selected from the range of 0.001 to 0.1, and the second positive electrode active material is electrically neutral.
[0139] The battery will be accompanied by Li deintercalation and consumption during the charge and discharge process, and the molar content of Li is different when the battery is discharged to different states. In the list of positive electrode materials in this application, the molar content of Li is the initial state of the material, that is, the state before feeding. The positive electrode material is used in the battery system, and the molar content of Li will change after charge and discharge cycles.
[0140] In the list of positive electrode materials in this application, the molar content of O is only a theoretical value. The release of oxygen from the lattice will cause the molar content of oxygen to change, and the actual molar content of O will fluctuate.
[0141] In some embodiments, the positive electrode film layer may also optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0142] In some embodiments, the positive electrode film layer may further include a conductive agent, for example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0143] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0144] [Electrolytes]
[0145] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.
[0146] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0147] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0148] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0149] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0150] [Isolation film]
[0151] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.
[0152] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0153] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.
[0154] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.
[0155] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0156] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 6 The secondary battery 5 is a square structure as an example.
[0157] In some embodiments, reference Figure 7 , the outer package may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0158] In some embodiments, secondary batteries may be assembled into a battery module. The number of secondary batteries contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.
[0159] Figure 8 4 is an example of a battery module. Figure 8 In the battery module 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.
[0160] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.
[0161] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.
[0162] Fig. 9 and Fig.10 1 is a battery pack 1 as an example. Fig. 9 and Fig.10 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.
[0163] In addition, the present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0164] As an electrical device, a secondary battery, a battery module or a battery pack can be selected according to its usage requirements.
[0165] Fig.11 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.
[0166] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.
[0167] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0168] [Dv50, Dv90 test method] The particles are measured using a laser diffraction particle size distribution measuring instrument according to the particle size distribution laser diffraction method (for details, please refer to GB / T19077-2016).
[0169] [Layer thickness test method] Obtain the TEM image of the negative electrode active material, select 20 points in different locations for the layer to be tested, obtain the thickness of the 20 points, and then calculate the average thickness as the thickness of the layer to be tested.
[0170] Example 1
[0171] 1. Preparation of negative electrode active materials
[0172] The silicon-tin-carbon negative electrode active material was prepared by direct current arc discharge using the NP450 equipment of Shenyang Beiyu Vacuum Equipment Co., Ltd.
[0173] (1) Micron-grade (Dv50 = 200 μm) silicon powder and tin powder (Dv50 = 200 μm) were mixed in a mass ratio of 7:3 and pressed into a cylindrical block with a diameter of 3 cm and a thickness of 1 cm. The block was placed on a copper base as the anode of the arc discharge, and the tungsten rod was used as the cathode. The distance between the two electrodes was adjusted to 10 mm.
[0174] (2) Evacuate the reaction chamber to about 10 -2 Pa, argon, hydrogen and methane were filled in a ratio of 2:1:0.5 to reach 2×10 4 Pa, 1×10 4 Pa and 0.5×10 4 Pa.
[0175] (3) Turn on the cooling water system, connect the power supply and start the arc, adjust the current to 90A and the voltage to 20V, stabilize the arc, and evaporate the bulk target. The arc starting time lasts for 0.5 hours to evaporate the bulk target.
[0176] (4) After the reaction is completed, turn off the power supply, wait until the temperature drops to room temperature, turn off the cooling water system, collect the powder, and obtain the silicon-tin-carbon negative electrode active material.
[0177] in, Figure 1 The SEM image of the obtained silicon-tin-carbon negative electrode active material is shown in FIG. Figure 1 It can be seen that its morphology is spherical with uniform particle size.
[0178] Figure 2 The TEM image of the silicon-tin-carbon negative electrode active material obtained is shown in FIG. Figure 2 It can be seen that the negative electrode active material prepared in the present application is a core-shell structure, and the carbon layer and the intermediate layer are respectively uniformly coated and have uniform thickness.
[0179] 2. Preparation of button lithium-ion battery
[0180]
Negative electrode
[0181] The above negative electrode active material, super carbon black as a conductive agent, and sodium carboxymethyl cellulose as a binder were mixed into a slurry at a mass ratio of 80:10:10, coated on an aluminum current collector to prepare a negative electrode film, and vacuum dried at 80°C for 12 hours. The dried film was cut into discs with a diameter of 14 mm as negative electrode sheets.
[0182]
Positive electrode
[0183] Lithium metal is used as the positive electrode.
[0184]
Electrolyte
[0185] The electrolyte LiPF6 was dissolved in a mixed solvent of EC / DMC with a volume ratio of 1:1 to form an electrolyte.
[0186]
Isolation film
[0187] Celgard 2400 isolation membrane.
[0188]
Preparation of button-type lithium-ion batteries
[0189] The prepared negative electrode plate, a metal lithium sheet as a positive electrode plate and an electrolyte are assembled into a button-type lithium-ion battery.
[0190] 3. Button lithium-ion battery performance test
[0191] The cycling performance and rate performance of button batteries were tested using Wuhan Landian (LAND2001A) electrochemical performance tester.
[0192] (1) Test of specific capacity, capacity retention rate and coulombic efficiency: Leave the assembled battery for 12 hours to allow the electrolyte to fully infiltrate the negative electrode. Then clamp the battery on the crocodile clip of the tester. Enter the test current and the mass of the active material, the number of cycles and the test voltage range, and the tester itself will display the battery's charge specific capacity and discharge specific capacity. The number of cycles is 100 times, the test voltage range is 0.01-2V, the current density is 100mA / g, the test current = current density * mass of active material, the mass of active material = slurry mass * 80%, and the slurry mass = wafer mass - blank collector mass.
[0193] The 100th charge specific capacity and discharge specific capacity values are recorded, wherein the discharge specific capacity value is the specific capacity value in the embodiment of the present application.
[0194] The charge capacity is divided by the discharge capacity, and then multiplied by 100%, which is the coulomb efficiency value in the embodiment of the present application.
[0195] The percentage of the ratio of the discharge capacity after 100 cycles to the initial cycle discharge capacity is the capacity retention rate.
[0196] (2) Rate performance test: Place the assembled battery aside for 12 hours to allow the electrolyte to fully infiltrate the negative electrode plate. Then clamp the battery on the crocodile clip of the tester. Input the test current and the mass of the active material, the number of cycles and the test voltage range, and the tester itself will display the battery's charge capacity and discharge capacity. The number of cycles is 100 times, the test voltage range is 0.01-2V, the current density is 2A / g, the test current = current density * mass of active material, the mass of active material = slurry mass * 80%, and the slurry mass = wafer mass - blank collector mass. Record the 100th charge capacity and discharge capacity values, where the discharge capacity value is the rate performance in the embodiment of the present application.
[0197] The battery performance test results obtained in Example 1 are as follows: Figure 3 , Figure 4 as well as Figure 5 shown.
[0198] The electrochemical performance test results show that the electrochemical performance of the negative electrode sheet corresponding to the silicon-tin-carbon negative electrode active material in Example 1 is the best. At a current density of 100 mA / g, after 100 cycles, Figure 3 The capacity can be maintained at 1694 mAh / g, and the coulombic efficiency is as high as 99.85%. Figure 4 As shown, the silicon-tin-carbon negative electrode active material in Example 1 also has good rate performance. When the current density is 2A / g, the capacity is as high as 897mAh / g.
[0199] Examples 2-11 and Comparative Examples 1-4
[0200] The differences in the preparation processes of Examples 1-11 and Comparative Examples 1-4 are shown in Table 1.
[0201] The difference between Comparative Example 1 and Example 1 is that during the preparation of the negative electrode active material, (2) the reaction chamber is evacuated to about 10 -2 Pa, argon and hydrogen were filled in a ratio of 2:1 to reach 2×10 4 Pa, 1×10 4 That is, in Comparative Example 1, no gaseous carbon source was introduced during the preparation of the negative electrode active material.
[0202] The only difference between Comparative Example 2 and Example 1 is that: during the preparation of the negative electrode active material, (1) (1) micron-grade (Dv50 = 200 μm) silicon powder is used to replace the tin powder, and a cylindrical block with a diameter of 3 cm and a thickness of 1 cm pressed by silicon powder is placed on a copper base as the anode of arc discharge, and a tungsten rod is used as the cathode, and the distance between the two electrodes is adjusted to 10 mm.
[0203] The only difference between Comparative Example 3 and Example 1 is that: during the preparation of the negative electrode active material, (1) (1) micron-grade (Dv50 = 200 μm) tin powder is used to replace silicon powder, and a cylindrical block with a diameter of 3 cm and a thickness of 1 cm pressed by tin powder is placed on a copper base as the anode of arc discharge, and a tungsten rod is used as the cathode, and the distance between the two electrodes is adjusted to 10 mm.
[0204] The difference between Comparative Example 4 and Example 1 is that: (2) the reaction chamber is evacuated to about 10 -2 Pa, hydrogen and methane were charged in a ratio of 1:0.5. That is, in comparative example 4, argon was not added in step (2).
[0205] Table 1 Differences in preparation process parameters
[0206]
[0207] The differences between the negative electrode active materials prepared in Examples 1-11 and Comparative Examples 1-4 are shown in Table 2.
[0208] Table 2 Differences in negative electrode active materials
[0209]
[0210] The test results of the negative electrode active materials prepared in Examples 1-11 and Comparative Examples 1-4 are shown in Table 3.
[0211] Table 3 Test results
[0212]
[0213]
[0214] It can be seen from Table 2 and Table 3 that the negative electrode active material provided in the embodiment of the present application not only has a high capacity, but also the lithium ion battery prepared from the negative electrode active material has better coulombic efficiency, rate performance and cycle life.
[0215] According to Examples 1-5, it can be seen that when the core and the intermediate layer account for the same total mass percentage in the negative electrode active material, the different mass ratios of the two will affect the performance of the negative electrode active material. Since the discharge specific capacity of silicon is greater than the discharge specific capacity of tin, but since the electronic conductivity of tin is higher than that of silicon, therefore, when the core and the intermediate layer account for the same total mass percentage in the negative electrode active material, as the mass ratio of silicon to tin gradually decreases, the capacity of the negative electrode active material gradually decreases, while the coulombic efficiency, capacity retention rate and rate performance all show a trend of first decreasing and then increasing.
[0216] According to Examples 1, 6-8, the mass percentage and thickness of the carbon layer in the negative electrode active material will affect the performance of the negative electrode active material. By controlling the thickness of the carbon layer to 3.5-4.5 nm, the negative electrode active material not only has a high capacity, but also the lithium ion battery prepared from the negative electrode active material has better coulombic efficiency, rate performance and cycle life.
[0217] According to Examples 1, 9 and 10, the material of the inner core of the negative electrode active material can be silicon, silicon dioxide or a first metal that can intercalate and deintercalate lithium, and the material of the middle layer is a second metal that can intercalate and deintercalate lithium. The negative electrode active material is based on its nanometer-scale particle size and the mutual cooperation of each layer in the core-shell structure, so that the negative electrode active material not only has a high capacity, but also the lithium ion battery prepared from the negative electrode active material has better rate performance and cycle life. The negative electrode active material prepared in Comparative Example 1 does not contain a carbon layer as a surface layer, resulting in the middle layer being directly exposed to the outside, which not only leads to a low discharge capacity of the negative electrode active material, but also leads to a low coulombic efficiency of the battery corresponding to the negative electrode active material, as well as poor rate performance and cycle life.
[0218] According to Example 1 and Comparative Examples 2-3, compared with the silicon-carbon two-layer core-shell structure and the tin-carbon two-layer core-shell structure, the silicon-tin-carbon three-layer core-shell structure provided in the present application is beneficial to significantly improve the discharge capacity of the negative electrode active material, and significantly improve the coulombic efficiency, rate performance and cycle life of the battery corresponding to the negative electrode active material.
[0219] According to Example 1 and Comparative Example 4, the particle size has a great influence on the performance of the negative electrode active material. Since the particle size of Comparative Example 4 is much larger than that of Example 1, its capacity is reduced, and the coulombic efficiency, rate performance and cycle life of the lithium-ion battery prepared from the negative electrode active material are all reduced compared with those of the examples.
[0220] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A negative electrode active material, characterized in that: The particle size of the negative electrode active material is less than or equal to 200 nm, and the negative electrode active material comprises: a core, an intermediate layer coated on the surface of the core, and a carbon layer coated on the surface of the intermediate layer; The material of the core includes silicon, silicon dioxide or a first metal capable of inserting and extracting lithium, and the material of the intermediate layer includes a second metal capable of inserting and extracting lithium, and the second metal is different from the first metal.
2. The negative electrode active material according to claim 1, characterized in that The negative electrode active material has a spherical morphology.
3. The negative electrode active material according to claim 1, characterized in that The melting point of the inner core is greater than the melting point of the middle layer.
4. The negative electrode active material according to any one of claims 1 to 3, characterized in that: The core is inserted and removed Li + The volume expansion rate of the intermediate layer is greater than that of the intermediate layer during the insertion and extraction of Li + The volume expansion rate of the intermediate layer is + The volume expansion rate of the carbon layer is greater than that of the carbon layer during the insertion and extraction of Li + volume expansion rate.
5. The negative electrode active material according to any one of claims 1 to 4, characterized in that: The electronic conductivity of the intermediate layer is 10 7 S / m-10 22 S / m.
6. The negative electrode active material according to any one of claims 1 to 5, characterized in that: The discharge specific capacities of the inner core and the middle layer are respectively greater than 900 mAh / g.
7. The negative electrode active material according to any one of claims 1 to 6, characterized in that: The core is silicon, and the middle layer is tin.
8. The negative electrode active material according to any one of claims 1 to 3, characterized in that: The inner core is aluminum, and the middle layer is tin.
9. The negative electrode active material according to any one of claims 1 to 8, characterized in that: The mass percentage of the core in the negative electrode active material is 70%-80%, the mass percentage of the intermediate layer in the negative electrode active material is 15%-20%, and the mass percentage of the carbon layer in the negative electrode active material is 5%-10%.
10. The negative electrode active material according to any one of claims 1 to 9, characterized in that: The thickness of the intermediate layer is 5nm-8nm; and / or, The thickness of the carbon layer is 3-5 nm.
11. The negative electrode active material according to any one of claims 1 to 10, characterized in that: The negative electrode active material has a Dv50 of 50nm-100nm and a Dv90 of 120nm-150nm.
12. The negative electrode active material according to any one of claims 1 to 11, characterized in that: The powder compaction density of the negative electrode active material at 3T is 1.3 g / cm 3 -1.7g / cm 3 .
13. A method for preparing a negative electrode active material, characterized in that: include: Mixing components for forming a core and an intermediate layer and pressing them into a block, wherein the component for forming the core comprises silicon, silicon dioxide or a first metal capable of inserting and extracting lithium, and the component for forming the intermediate layer comprises a second metal capable of inserting and extracting lithium, and the melting point of the core is greater than the melting point of the intermediate layer; The block is placed as an anode target on the anode, a tungsten rod or a carbon rod is used as a cathode, and a direct current arc discharge plasma treatment is performed in an atmosphere of hydrogen, an inert gas and a gaseous carbon source to obtain the negative electrode active material; Wherein, the gaseous carbon source includes at least one of alkanes, alkenes and alkynes.
14. The preparation method according to claim 13, characterized in that: The gaseous carbon source is calculated based on methane, and the volume ratio of the inert gas, the hydrogen and the gaseous carbon source is 1.5-2.5:1:0.4-0.
6.
15. A secondary battery, characterized in that: The invention comprises the negative electrode active material according to any one of claims 1 to 12 or the negative electrode active material prepared by the preparation method according to any one of claims 13 to 14.
16. An electrical device, characterized in that: Includes the secondary battery as claimed in claim 15.
Citation Information
Patent Citations
Anode for lithium ion secondary battery, production method thereof, and lithium ion secondary battery
CN101593828A
Carbon-coated silicon nanoparticle, preparation method and application thereof
CN112234173A
Silicon-tin composite negative electrode material and preparation method thereof
CN114843466A
Silicon-metal oxide composite material, method for manufacturing same, secondary
CN116314833A
Negative electrode active material, negative electrode, secondary battery and electric device
CN116344780A
Cited By
Preparation method of lithium nickel manganese oxide positive electrode active material, battery monomer, battery device and power utilization device
CN120809813A